Skin disease in goats (Capra aegagrus hircus): a retrospective study of 358 cases at a university veterinary teaching hospital (1988–2020). Issue 3 (27th December 2021) - White, Stephen D.; Affolter, Verena K.; Molinaro, Annette M.; Depenbrock, Sarah M.; Chigerwe, Munashe; Heller, Meera C.; Rowe, Joan Dean
Abstract : Background: Goats are important worldwide as a source of milk, meat, fibre and hide, and as show animals and pets. Hypothesis/objectives: To document the type, signalment associations and prevalence of skin disease in a referral hospital population. Animals: Case population at a university veterinary teaching hospital. Methods and materials: Retrospective study by searching computerised medical records of goats seen between 1 January 1988 and 1 January 2021. Key words employed were "alopecia, caseous lymphadenitis, Chorioptes, dermatitis, dermatophyte, dermatophytosis, goat, lice, louse, mange, mite, pemphigus foliaceus, Psoroptes, ringworm, seborrhea, skin" Results: Of 1, 488 records reviewed, 358 (24%) goats had skin disease recorded. Seventy‐nine (22.1%) of 358 goats presented primarily for skin disease. The Nigerian Dwarf goat breed was at higher risk of developing skin disease ( P < 0.0002). As goats aged, the odds for developing skin disease was higher [odds ratio (OR) = 1.07 per year, 95% confidence interval (1.04, 1.12)] as was the predilection for malignant skin tumours ( P < 0.001). Sex was not associated with skin disease ( P = 0.98). The most common clinical sign was exfoliative dermatitis, noted in 94 (26.4%) of 358 goats. The most common diagnoses were pediculosis, bacterial skin disease and squamous cell carcinoma. Less frequent diagnoses were Chorioptes spp. infestation, contagious ecthyma (orf), coronitis/interdigital dermatitis, demodicosis, dermatophytosis, Psoroptes spp. infestation, dermatophilosis and pemphigus foliaceus. Conclusions and clinical importance: Skin diseases are common in goats. Nigerian Dwarf goats and older goats are at greater risk of developing skin disease; Nigerian Dwarf goats had a predilection for malignant skin tumours. Clinicians should include a dermatological examination in goats regardless of the reason for presentation. Abstract : Background – Goats are important worldwide as a source of milk, meat, fibre and hide, and as showing animals and pets. Hypothesis/objectives – To document the type, signalment associations and prevalence of skin disease in a referral hospital population. Conclusions and clinical importance – Skin diseases are common in goats. Nigerian Dwarf goats and older goats are at greater risk of developing skin disease; Nigerian Dwarf goats had a predilection for malignant skin tumours. Clinicians should include a dermatological examination in goats regardless of the reason for presentation. Résumé: Contexte: Les chèvres sont importantes dans le monde entier en tant que source de lait, de viande, de fibres et de peau, et en tant qu'animaux de cirque et animaux de compagnie. Hypothèse/objectifs: Documenter le type, les associations de signalisation et la prévalence des maladies de la peau dans une population hospitalière de référence Animaux: Population de cas dans un CHU vétérinaire. Méthodes et matériels: Étude rétrospective par recherche des dossiers médicaux informatisés de caprins vus entre le 1er janvier 1988 et le 1er janvier 2021. Les mots clés employés étaient « alopécie, lymphadénite caséeuse, Chorioptes, dermatite, dermatophyte, dermatophytose, chèvre, poux, pou, gale, acarien, pemphigus foliacé, Psoroptes, teigne, séborrhée, peau ». Résultats: Sur 1 488 dossiers examinés, 358 (24 %) chèvres présentaient une dermatose. Soixante‐dix‐neuf (22, 1 %) des 358 chèvres se sont présentées principalement pour une maladie de peau. La race de chèvre naine nigériane était plus à risque de développer une maladie de peau ( P < 0, 0002 ). À mesure que les chèvres vieillissaient, les risques de développer une dermatose étaient plus élevés [ratio (OR) = 1, 07 par an, intervalle de confiance à 95 % (1, 04, 1, 12)], tout comme la prédilection pour les tumeurs malignes de la peau ( P < 0, 001 ). Le genre n'était pas associé à une maladie de peau ( P = 0, 98 ). Le signe clinique le plus fréquent était la dermatite exfoliative, notée chez 94 (26, 4 %) des 358 chèvres. Les diagnostics les plus fréquents étaient la pédiculose, la dermatose bactérienne et le carcinome épidermoïde. Les diagnostics moins fréquents étaient une infestation à Chorioptes spp ., ecthyma contagieux (orf), coronite/dermatite interdigitale, démodécie, dermatophytose, une infestation à Psoroptes spp ., dermatophilose et pemphigus foliacé. Conclusions et importance Clinique: Les maladies de peau sont fréquentes chez les chèvres. Les chèvres naines nigérianes et les chèvres plus âgées sont plus à risque de développer une maladie de peau; les chèvres naines nigérianes avaient une prédilection pour les tumeurs cutanées malignes. Les cliniciens doivent inclure un examen dermatologique des chèvres, quelle que soit le motif de consultation. Resumen: Introducción: las cabras son importantes en todo el mundo como fuente de leche, carne, fibra y cuero, y como animales de exhibición y mascotas. Hipótesis/objetivos: documentar el tipo, las asociaciones en la presentación clínica y la prevalencia de enfermedades de la piel en una población de un hospital veterinario de referencia. Animales: casos recibidos en un hospital veterinario universitario de enseñanza. Métodos y materiales: estudio retrospectivo mediante la búsqueda de registros médicos en la base de datos de cabras atendidas entre el 1 de enero de 1988 y el 1 de enero de 2021. Las palabras clave empleadas fueron "alopecia, linfadenitis caseosa, corioptes, dermatitis, dermatofito, dermatofitosis, cabra, piojos, piojo, sarna, ácaro, pénfigo foliáceo, psoroptes, tiña, seborrea, piel " Resultados: de 1, 488 entradas revisadas, 358 (24%) cabras tenían enfermedades de la piel registradas. Setenta y nueve (22, 1%) de 358 cabras se presentaron principalmente por enfermedades de la piel. La raza de cabra enana nigeriana presentó un mayor riesgo de desarrollar enfermedades de la piel ( P <0, 0002). A medida que las cabras envejecían, las probabilidades de desarrollar enfermedades de la piel eran mayores [razón de probabilidades (OR) = 1, 07 por año, intervalo de confianza del 95% (1, 04; 1, 12)] al igual que la predilección por los tumores cutáneos malignos ( P <0.001). El sexo no se asoció con enfermedades de la piel ( P = 0, 98). El signo clínico más común fue la dermatitis exfoliativa, que se observó en 94 (26, 4%) de 358 cabras. Los diagnósticos más frecuentes fueron pediculosis, enfermedad cutánea bacteriana y carcinoma de células escamosas. Los diagnósticos menos frecuentes fueron infestación con Chorioptes spp ., ectima contagioso (orf), coronitis/dermatitis interdigital, demodicosis, dermatofitosis, infestación con Psoroptes spp ., dermatofilosis y pénfigo foliáceo. Conclusiones e importancia clínica: Las enfermedades de la piel son comunes en las cabras. Las cabras enanas nigerianas y las cabras más viejas tienen un mayor riesgo de desarrollar enfermedades de la piel; las cabras enanas nigerianas mostraron mayor riesgo de desarrollar tumores cutáneos malignos. Los veterinarios deben incluir un examen dermatológico en cabras independientemente del motivo de presentación. Zusammenfassung: Hintergrund: Ziegen haben weltweit eine Bedeutung als Milchquelle, bei der Fleischproduktion, bei der Faser‐ und Lederproduktion und als Show‐ und Haustiere. Hypothese/Ziele: Eine Dokumentation des Typs, der Zusammenhänge mit dem Signalement und dem Auftreten von Hauterkrankungen in der Population einer Überweisungsklinik. Tiere: Die Fälle stammten aus der Population einer veterinärmedizinischen Lehranstalt. Methoden und Materialien: Es wurde eine retrospektive Studie durchgeführt, bei der die elektronischen medizinischen Karteien von Ziegen, die zwischen dem 1. Jänner 1988 und dem 1. Jänner 2021 vorgestellt wurden, durchgesehen wurden. Die verwendeten Schlüsselwörter waren „Alopezie, käsige Lymphadenitis, Chorioptes, Dermatitis, Dermatophyt, Dermatophytose, Ziege, Läuse, Räude, Milbe, Pemphigus foliaceus, Psoroptes, Ringworm, Seborrhoe, Haut". Ergebnisse: Von den 1488 durchgesehenen Karteien war bei 358 (24%) der Ziegen eine Hautkrankheit beschrieben. Neunundsiebzig (22, 1%) der 358 Ziegen wurden hauptsächlich wegen einer Hauterkrankung vorgestellt. Die Nigerianische Zwergziege hatte ein höheres Risiko eine Hautkrankheit zu entwickeln ( P < 0, 0002). Mit zunehmendem Alter der Ziegen war die Wahrscheinlichkeit eine Hauterkrankung zu entwickeln höher [Odds Ration (OR)= 1, 07 pro Jahr, Konfidenzintervall 95% (1, 04; 1, 12)], ebenso wie die Prädilektion für maligne Hauttumoren ( P < 0, 001). Das Geschlecht stand mit der Hauterkrankung nicht im Zusammenhang ( P = 0, 98). Die häufigsten klinischen Zeichen waren eine exfoliative Dermatitis, die bei 94 (26, 4%) der 358 Ziegen festgestellt wurde. Die häufigsten Diagnosen waren Pedikulose, bakterielle Hauterkrankung und Plattenepithelkarzinom. Weniger häufige Diagnosen waren ein Chorioptes spp. Befall, Ecthyma contagiosum (orf), Coronitis/Interdigitale Dermatitis, Demodikose, Dermatphytose, Psoroptes spp. Befall, Dermatophilose und Pemphigus foliaceus. Schlussfolgerungen und klinische Bedeutung: Hauterkrankungen treten bei Ziegen häufig auf. Die Nigerianischen Zwergziegen weisen ein höheres Risiko auf eine Hauterkrankung zu entwickeln. KlinikerInnen sollten bei Ziegen immer eine dermatologische Untersuchung durchführen, egal aus welchem Grund sie vorgestellt werden. 要約: 背景: ヤギは、乳、肉、線維、獣皮の供給源として、また、展示用動物やペットとして、世界中で重要な動物である。 仮説・目的: 本研究の目的は、紹介病院集団における皮膚疾患の種類、シグナルメントの関連性、有病率を記録することであった。 被検動物: 大学の獣医学教育機関における症例群。 材料と方法: 1988年1月1日から2021年1月1日までに受診したヤギのコンピュータ医療記録を検索することによる回顧的研究。キーワードは "脱毛症、乾酪性リンパ節炎、ショクヒヒゼンダニ、皮膚炎、皮膚糸状菌、皮膚糸状菌症、ヤギ、シラミ、疥癬、ダニ、落葉状天疱瘡、キュウセンヒゼンダニ、白癬、脂漏、皮膚 "とした。 結果: レビューした1, 488件の記録のうち、358頭（24%）のヤギに皮膚病の記録があった。358頭のヤギのうち79頭（22.1％）が主に皮膚病で来院していた。ナイジェリアン・ドワーフ・ゴートは、皮膚病を発症するリスクが高かった（P < 0.0002）。ヤギが高齢になると、皮膚疾患を発症する確率が高くなり［オッズ比（OR）＝1年あたり1.07、95％信頼区間（1.04、1.12）］、皮膚の悪性腫瘍が発生しやすくなった（P < 0.001）。性別と皮膚疾患との関連はなかった（P = 0.98）。最も一般的な臨床症状は剥脱性皮膚炎で、358頭のヤギのうち94頭（26.4%）に認められた。最も多い診断名は、シラミ、細菌性皮膚疾患、扁平上皮癌であった。頻度が低かったのは、ショクヒヒゼンダニ属感染、伝染性膿疱性皮膚炎（orf）、蹄冠炎／指間皮膚炎、毛包虫症、皮膚糸状菌症、キュウセンヒゼンダニ属感染、デルマトフィルス症、落葉状天疱瘡であった。 結論と臨床的重要性: 皮膚疾患はヤギにおいて一般的である。ナイジェリアン・ドワーフ・ゴートや高齢のヤギは皮膚疾患を発症するリスクが高い。ナイジェリアン・ドワーフ・ゴートは悪性皮膚腫瘍を好む傾向がある。臨床家は来院理由に関わらず、ヤギの皮膚科的検査を行うべきである。 摘要: 背景: 山羊在世界范围内作为羊奶、肉类、纤维和皮革的主要来源，也是重要的展示动物和宠物。 假设/目的: 记录转诊医院种群中皮肤病的类型、有关症状和发病率 动物: 大学兽医教学医院的病例种群。 方法和材料: 通过1988年1月2021年1月1月1日期间电脑病历检索山羊进行回顾性研究。采用的关键词为"脱毛、干酪性淋巴结炎、皮螨、皮炎、皮肤癣菌、皮肤癣菌病、山羊、虱子（lice）、虱子（louse）、螨、螨虫、落叶型天疱疮、痒螨、癣、皮脂溢、皮肤" 结果: 在调查的1, 488份记录中，358只(24%)山羊记录有皮肤病。358只山羊中有79只(22.1%)主要表现为皮肤病。尼日利亚矮山羊品种发生皮肤病的风险较高(P < 0.0002)。随着山羊年龄的增长，发生皮肤病的几率更高[比值比(OR)= 1.07/年，95%置信区间(1.04，1.12)]，恶性皮肤肿瘤的易感性也是如此(P < 0.001)。性别与皮肤病无关(P = 0.98)。最常见的临床体征为剥脱性皮炎，358只山羊中的94只(26.4%)可见该症状。最常见的诊断为虱病、细菌性皮肤病和鳞状细胞癌。不太常见的诊断是皮螨侵扰，传染性脓疱(羊痘)、冠周炎/趾间炎、蠕形螨病、皮肤癣菌病、痒螨侵扰、嗜皮菌病和落叶型天疱疮。 结论和临床重要性: 皮肤病在山羊中很常见。尼日利亚矮山羊和老年山羊发生皮肤病的风险更大；尼日利亚矮山羊易感恶性皮肤肿瘤。无论山羊就诊原因如何，临床医生应进行皮肤科检查。 Resumo: Contexto: As cabras são importantes mundialmente pela sua produção de leite, carne, fibra e couro, bem como animais de exposição e pets. Hipótese/objetivos: Documentar o tipo, sinais clínicos associados e prevalência de dermatopatias em cabras em uma população de um hospital de referência. Animais: Casuística de um hospital veterinário universitário. Resultados: Dos 1.488 casos prontuários revisados, 358 (24%) cabras apresentavam histórico de doença de pele. Setenta e sete (22, 1%) das 358 cabras apresentaram doença cutânea primária. As cabras anãs nigerianas apresentaram maior risco de desenvolver dermatopatias ( P <0, 0002). À medida que as cabras envelheciam, o risco de desenvolver doenças de pele foi aumentando [odds ratio (OR) = 1, 07 por ano, intervalo de confiança de 95% (1, 04‐1, 12)], assim como a predisposição a desenvolver tumores de pele malignos ( P <0, 001). Não houve associação de sexo a doenças de pele ( P = 0, 98). O sinal clínico mais comum foi dermatite esfoliativa, observada em 94 (26, 4%) de 358 cabras. Os diagnósticos mais comuns foram pediculose, piodermite bacteriana e carcinoma de células escamosas. Os diagnósticos menos frequentes foram infestação por Chorioptes spp., ectima contagioso (orf), coronite/dermatite interdigital, demodiciose, dermatofitose, infestação por Psoroptes spp., dermatofilose e pênfigo foliáceo. Conclusões e importância clínica: Doenças de pele são comuns em cabras. As cabras anãs nigerianas e cabras idosas apresentam maior risco de desenvolver dermatopatias; as cabras anãs nigerianas possuem predisposição a tumores cutâneos malignos. Os clínicos devem incluir avaliação dermatológica nas cabras em todas as consultas, independente da queixa principal.